Producer dynamics : new evidence from micro data - Dunne, Timothy; Jensen, J. Bradford; Roberts, Mark J. (Studies in income and wealth, 2009)
The Census Bureau has recently begun releasing official statistics that measure the movements of firms in and out of business and workers in and out of jobs. The economic analyses in Producer Dynamics exploit this newly available data on establishments, firms, and workers, to address issues in industrial organization, labor, growth, macroeconomics, and international trade. This innovative volume brings together a group of renowned economists to probe topics such as firm dynamics across countries; patterns of employment dynamics; firm dynamics in nonmanufacturing industries such as retail, heal.